The Influence of Talent Management, Compensation, Leadership Support, and Work Environment on Employee Retention - Rama, Rovanita; Yusuf, Ramdan (International Journal of Business, Law, and Education, 2026)
Employee retention has become a critical issue for organizations seeking to maintain stability and achieve long-term success in a competitive business environment. This study aims to examine the influence of talent management, compensation, leadership support, and work environment on employee retention. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 150 employees through a structured questionnaire measured on a Likert scale. The data were analyzed using descriptive statistics and multiple regression analysis to determine the relationships between variables. The results indicate that talent management, compensation, leadership support, and work environment simultaneously have a significant effect on employee retention. Partially, all variables were found to have positive and significant influences, with talent management emerging as the most dominant factor. These findings suggest that organizations should prioritize employee development, provide fair and competitive compensation, strengthen leadership practices, and create a supportive work environment to enhance employee retention. This study contributes to the existing literature by providing empirical evidence on the combined effects of these factors and offers practical implications for organizational strategies aimed at reducing employee turnover.